2020
DOI: 10.3389/fneur.2020.00869
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension in the United States: Demographic and Socioeconomic Disparities

Abstract: Background: Obesity's risk increases for low-income, female, young, and Black patients. By extrapolation, idiopathic intracranial hypertension (IIH)-a disease associated with body mass index-would potentially display socioeconomic and demographic disparities. Methods: IIH incidence (per 100,000) was investigated with respect to sex, age, income, residence, and race/ethnicity, by querying the largest United States (US) healthcare administrative dataset (1997-2016), the National (Nationwide) Inpatient Sample. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
0
31
0
1
Order By: Relevance
“…Idiopathic intracranial hypertension (IIH) is characterized by raised intracranial pressure (ICP) that causes chronic headaches and papilledema with the risk of permanent visual loss. [1][2][3] Both the incidence and prevalence of IIH in preceding decades has increased, [4][5][6] linked with the worldwide obesity epidemic. 7 Modest weight gain (approximately 5% were people with obesity) is associated with an increased risk of developing IIH, and in those people who do not have obesity, recent weight gain is a risk.…”
Section: Classification Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Idiopathic intracranial hypertension (IIH) is characterized by raised intracranial pressure (ICP) that causes chronic headaches and papilledema with the risk of permanent visual loss. [1][2][3] Both the incidence and prevalence of IIH in preceding decades has increased, [4][5][6] linked with the worldwide obesity epidemic. 7 Modest weight gain (approximately 5% were people with obesity) is associated with an increased risk of developing IIH, and in those people who do not have obesity, recent weight gain is a risk.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…Idiopathic intracranial hypertension (IIH) is characterized by raised intracranial pressure (ICP) that causes chronic headaches and papilledema with the risk of permanent visual loss. 1 - 3 Both the incidence and prevalence of IIH in preceding decades has increased, 4 - 6 linked with the worldwide obesity epidemic. 7 …”
mentioning
confidence: 99%
“…We also found that highest educational level was much lower in IIH patients compared to GP controls. It has been reported that IIH seems to affect socioeconomic groups differently with higher risk of IIH in socially deprived groups (2,18,23), possibly due to inequalities in healthcare that should be highlighted.…”
Section: Incidencementioning
confidence: 99%
“…[1] [6] The disease is more common in those who are socially disadvantaged. [6] [9] Important principles for the management of IIH have been agreed [1] where modifying the underlying pathophysiology, with weight management is key for all patients with typical disease and a raised body mass index. [4] In those with rapidly declining visual function, now between 7-9% of those with IIH [6], an emergency intervention is warranted to save sight.…”
Section: Expert Commentary 1 Introductionmentioning
confidence: 99%